Proceedings of the 2024 5th International Conference on Big Data and Informatization Education (ICBDIE 2024) - Miao Yu; Kannimuthu Subramaniyam; Mohammad Akour; Hafizoah Kassim (Atlantis Press International BV, 2024)
This is an open access book. Big data is a large-scale and complex data set based on modern information technology. It has the characteristics of scale and diversity, and its information processing and storage capabilities have been significantly improved. The application of big data technology is to fully mine and analyze data, build cooperation and interaction between teachers and students, encourage students to communicate and interact with teachers, and give full play to the education and teaching effect of big data. In order to improve teaching quality and efficiency as much as possible, all kinds of teaching in the new era must have strong flexibility and foresight, so as to adapt to the development of modern society. So big data will give greater flexibility to educational activities. Therefore, big data will give greater flexibility to educational activities, and more and more scholars provide new ideas for the above research directions. To sum up, we will hold an international academic conference on big data and information education. The 2024 5th International Conference on Big Data and Informatization Education (ICBDIE2024) will be held on January 19–21, 2024 in Sanya, China. ICBDIE 2024 is to bring together innovative academics and industrial experts in the field of Big Data and Informatization Education to a common forum. The primary goal of the conference is to promote research and developmental activities in Big Data and Informatization Education and another goal is to promote scientific information interchange between researchers, developers, engineers, students, and practitioners working all around the world. The conference will be held every year to make it an ideal platform for people to share views and experiences in international conference on Big Data and Informatization Education and related areas.